PENGABDIAN KEPADA MASYARAKAT MELALUI PEMERIKSAAN KESEHATAN & PENYULUHAN : PENGENDALIAN HIPERTENSI DAN MANAJEMEN STRESS - WATANIA, LANI NATALIA; Fangidae, Erniyati; Fransiska, Juwita; Hasibuan, Shinta; Sitorus, Fiolenty; Tahulending, Peggy (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2023)
Abstract The increasing rate of hypertension in the elderly is on an increasing trend. This is due to an increase in the number of elderly population. Hypertension has a dangerous impact on the elderly. Hypertension can also be controlled. The importance of controlling hypertension by maintaining a healthy lifestyle. The purpose of this community services was to increase the understanding of the people of Kadu Tangerang Village in controlling hypertension and how to manage stress. Method that can be implemented at this time were to provide education on how to control hypertension. The respondent of this community service were community in RW 003 Kadu Village, Curug, Tangerang, with 61 elderly people. The methods of activities carried out to achieve the objectives of the community service are health checks and health education. The results of the activity indicate an increase in the community knowledge about hypertension control and stress management. Community service activities in the form of health education are expected to be one of the strategies in controlling hypertension so as to avoid complications and improve the quality of life of the elderly and their families. Keywords: Hypertension, Elderly, Stress Management, Healthy Life-style